2018
DOI: 10.3390/ma11040582
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Fabrication of Morphology-Controlled Polymeric Microspheres of Blends of Poly(4-butyltriphenylamine) and Poly(methyl methacrylate)

Abstract: Multicomponent polymer particles with specific morphology are promising materials exhibiting novel functionality which cannot be obtained with single-component polymer particles. Particularly, the preparation of such kinds of polymer particles involving electrically or optically active conjugated polymers with uniform size is a challenging subject due to their intense demands. Here, microspheres of binary polymer blend consisting of poly(4-butyltriphenylamine) (PBTPA)/poly(methyl methacrylate) (PMMA) (1:1 in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Other polymer/BCP mixtures offer opportunities to generate unique particle structures; Zhu et al reported that addition of poly­(styrene)- b -poly­(ethylene oxide) (PS- b -PEO) to PS/chloroform droplets yielded foam-like, nodular (vesicular) and spiky microparticles following solvent extraction. Varying the solvent removal rate and composition of droplets from mixtures of poly­(4-butyltriphenylamine) (PBTPA), poly­(methyl methacrylate) (PMMA), and poly­(4-butyltriphenylamine)- b -poly­(methyl methacrylate) (PBTPA- b -PMMA) has been shown to generate a range of spherical, core–shell, Janus, and internally phase-separated particle structures. , …”
Section: Droplet Solvent Extraction (Dse)mentioning
confidence: 99%
See 2 more Smart Citations
“…Other polymer/BCP mixtures offer opportunities to generate unique particle structures; Zhu et al reported that addition of poly­(styrene)- b -poly­(ethylene oxide) (PS- b -PEO) to PS/chloroform droplets yielded foam-like, nodular (vesicular) and spiky microparticles following solvent extraction. Varying the solvent removal rate and composition of droplets from mixtures of poly­(4-butyltriphenylamine) (PBTPA), poly­(methyl methacrylate) (PMMA), and poly­(4-butyltriphenylamine)- b -poly­(methyl methacrylate) (PBTPA- b -PMMA) has been shown to generate a range of spherical, core–shell, Janus, and internally phase-separated particle structures. , …”
Section: Droplet Solvent Extraction (Dse)mentioning
confidence: 99%
“…The lowest energy structures are not necessarily determined by minimization of interfacial energies and therefore are not always spherical; mechanical instabilities can occur, triggered by the compressive stresses occurring during internal volume reduction of a soft-solid or viscoelastic skin, or gradient multilayered profile, and resulting in folding, buckling, irregular polyhedral, and higher aspect ratio shape formation, illustrated in Figure , parts f and g, or even completely collapsed and crumpled particles . Further modulation can be achieved by doping with colloids into the polymer solution droplets, driving more complex thermodynamic and mechanic pathways, and can result in a variety of bicontinuous structures encapsulating colloidal clusters and external particle shapes, shown in Figure h. , With added components such as BCPs, the kinetics and thermodynamics of self-assembly, interfacial stabilization and spatial segregation of individual species within multicomponent droplets during drying give rise to a wide range of complex, hierarchical and (often) anisotropic particle structures. , Ku et al have comprehensively reviewed the topic of BCP particles. Here, we highlight two such structures based on polymer/BCP blends where the self-assembly of BCPs during drying-induced interfacial instabilities lead to striking particle morphologies, as seen in the nodular (“budding vesicular”) and spiky particle structures in Figure , parts i and j …”
Section: Droplet Solvent Extraction (Dse)mentioning
confidence: 99%
See 1 more Smart Citation
“…argued that the effect of molecular weight on the mobility of the polymer also plays an important role in determining the particle morphology. Reducing the molecular weight of PMMA in the dispersed phase accelerates the translational speed of the PMMA‐rich phase and enables the engulfing of PBTPA polymer by PMMA polymer, which changes its morphology from an spherical Janus structure to an incomplete core‐shell structure, as shown in Figure 2d [32] …”
Section: Morphology Controlmentioning
confidence: 99%
“…Functional polymeric microspheres, which are often used in chemical catalysis and adsorption, have some special advantages, including a large specific surface area, strong adsorption capacity, surface reaction ability, and ease of modification [1,2], tumor embolization [3,4], information transfer [5], chromatographic separation [6], and biomedicine [7]. Transcatheter arterial embolization (TAE) was first reported by Yamamoto et al [8] in 1991, which was an effective technique for the insertion of a catheter into a target tissue or organ.…”
Section: Introductionmentioning
confidence: 99%